Metodologi Pembelajaran Pendidikan Agama Islam (PAI) Berbasis Ontologi: Integrasi Tarbiyah, Ta’lim, dan Ta’dib - Ika Irmawansah; Dewi mariatus solikah (Amaliyatu Tadris (AMYTA), 2026)
Islamic Religious Education (PAI) is currently facing a paradigmatic crisis due to the dominance of pragmatism and technocratism in modern education. These paradigms reduce PAI learning to an instrumental activity oriented toward cognitive achievement, administrative indicators, and procedural efficiency, thereby neglecting the reflective, ethical, and spiritual dimensions that constitute the core of Islamic education. This article aims to reconstruct the methodology of PAI learning by grounding it in the ontological foundation of Islamic education through the integration of the concepts of tarbiyah, ta‘lim, and ta’dib. This study employs a qualitative approach using library research and is analyzed through a philosophical-critical perspective. The findings indicate that the dominance of pragmatism and technocratism is rooted in an immanent and reductionistic ontology that marginalizes the inner and transcendent dimensions of the human being. As an alternative, the ontology of Islamic education positions humans as moral and spiritual subjects who develop holistically. The integration of tarbiyah as a process of nurturing human potential, ta‘lim as the development of reflective reasoning and Islamic literacy, and ta’dib as an ethical orientation toward the formation of adab, constructs a dialogical, reflective, and emancipatory methodological framework for PAI learning. Pembelajaran Pendidikan Agama Islam (PAI) menghadapi krisis paradigmatik akibat dominasi pragmatisme dan teknokratisme pendidikan modern. Kedua paradigma tersebut mereduksi pembelajaran PAI menjadi aktivitas instrumental yang berorientasi pada capaian kognitif, indikator administratif, dan efisiensi prosedural, sehingga mengabaikan dimensi reflektif, etis, dan spiritual yang merupakan inti pendidikan Islam. Artikel ini bertujuan merekonstruksi metodologi pembelajaran PAI dengan bertolak dari landasan ontologis pendidikan Islam melalui integrasi konsep tarbiyah, ta‘lim, dan ta’dib. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian kepustakaan (library research) dan dianalisis menggunakan pendekatan filosofis-kritis. Hasil kajian menunjukkan bahwa dominasi pragmatisme dan teknokratisme berakar pada ontologi imanen dan reduksionistik yang menyingkirkan dimensi batin dan transenden manusia. Sebagai alternatif, ontologi pendidikan Islam menempatkan manusia sebagai subjek moral dan spiritual yang berkembang secara holistik. Integrasi tarbiyah sebagai proses penumbuhan potensi insani, ta‘lim sebagai pengembangan nalar dan literasi keislaman yang reflektif, serta ta’dib sebagai orientasi etis pembentukan adab, membentuk kerangka metodologis pembelajaran PAI yang dialogis, reflektif, dan emansipatoris.